Studies of transient free radicals in solution by flash photolysis E.S.R - Simpson, N; Simpson, Nigel James Keiller (1990)
﻿ An introduction is presented to the nature of polarized and non-polarized transient spin resonance signals, produced by flash-photolysis e.s.r., followed by a description of the equipment used for experimental work. Theories of Chemically Induced Dynamic Electron Spin Polarization are reviewed and various models introduced to illustrate these concepts. A description is given of the first thorough investigation into the effect of CIDEP polarization transfer down a free radical chain and expands upon the consequences of hyperfine-dependent relaxation and the relative signs of coupling constants in various radical species. It concludes with an account of two methods of kinetic analysis which are the first practical demonstrations of their kind, and employ extension of expressions developed in earlier chapters. Studies are made of the CIDEP behaviour of radicals in high viscosity paraffins. A reassessment of previous published work is made: anomalous polarization behaviour was found to have been over-compensated for. A new method of extracting values for T1 and T2,/sub> is demonstrated for strong transient e.s.r. signals. A collection of experimental data relating to the previously unexplained absorptive polarization observed in the spectrum of ketyl radicals and the longer-time phase inversion of hyperfine-dependent CIDEP is given. The operation of Triplet Mechanism CIDEP in the ketyl radical systems is ruled out and a division of radicals into geminately formed and free-encounter pairs is shown to be incapable of explaining the observed phase changes. In its place a cross-relaxational mechanism, drawing upon simultaneously generated nuclear spin polarization is advanced. Conclusions are drawn that this may account for both anomalies. Lastly a photochemical application of CIDEP is demonstrated; two different reaction intermediates are identified upon photolysis of ortho phthalaldehyde, depending upon the quenching conditions. A reaction scheme consistent with all experimental data is proposed. A brief comment upon the photo-chemistry of indan 2-one concludes this work.